Relationship Between Regional Revenue and Expenditures: A Canonical Correlation Analysis - Payapo, Rukmuin; Ramly, Fahrudin; Bugis, Muhammad (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research aims to determine the relationship between regional revenues and regional expenditures. To achieve this, the method of canonical correlation analysis is employed. The research results show that in terms of regional revenues, regional income (Pendapatan Asli Daerah or PAD), general allocation funds (Dana Alokasi Umum or DAU) and gross regional domestic product (Produk Domestik Regional Bruto or PDRB) do not have a significant relationship. On the other hand, concerning regional expenditures, population size demonstrates a significant relationship, whereas routine expenditure and capital expenditure do not exhibit significance. It is noteworthy that the influence of regional spending on regional revenue surpasses the influence of regional revenue on regional spending. This implies that the government, in collaboration with the legislative body, is significantly influenced by the targeted regional spending in determining the regional revenue amount.